(untitled) - Misra, Prasanta K. (Burlington, MA, 2012)
The book begins with a clear, coherent picture of simple models of solids and properties and progresses to more advanced properties and topics later in the book. It offers a comprehensive account of the modern topics in condensed matter physics by including introductory accounts of the areas of research in which intense research is underway. The book assumes a working knowledge of quantum mechanics, statistical mechanics, electricity and magnetism and Green's function formalism
Keywords: Atomic physics,Vật lý nguyên tử,Chất ngưng tụ,Condensed matter